Integrated information about the multifaceted performance of the entity - Kabalski, Przemysław (Comparative Economic Research. Central and Eastern Europe, 2010)
The objective of the paper is to present a proposal concerning the scope and structure of information made available to external users about various aspects of business entities' performance, as well as to ascertain if the largest Polish listed companies disclose comprehensive and balanced information about their performance. Research has revealed that such information is published on a very limited scale.